(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Feminine word is related to women or girl and it’s considered suitable for them. The word feminine is used for the inner units of the self and sensibility in the fragrance of an artist’s personality. It means an artist’s (women) is identified and distinguished by their sensibility that is self- identity. Feminism is used to describe political, cultural or economic movement aimed for establishing equal rights and legal protection for women in society. Girish Karnad’s plays are very significant from feministic point of view. His plays ridicule the unjust values of the patriarchal society which does not care for the feelings of a woman and considers her a sub- ordinate that exists only to serve him with absolute loyalty. The plays – The Fire and the Rain and Naga-Mandala these elements are all there to serve the purpose of the dramatist. The paper highlights the pathetic condition under gone by the women characters in selected play of Girish Karnad. The paper present Girish Karnad effort to redefine the position of women in the society that has always limited their opportunities. His feminist sensibility is allowing his heroines to struggle for their identity with respect. He presents truth about human life and emotions contained in ancient Indian stories with alteration of social or moral values and modern norms.